Population Analysis of Skipjack Tuna (Katsuwonus pelamis) in the Waters of Cendrawasih Bay - Hukubun, Barnabas; Rapi, Nuraeni L.; Fatmawati , Fatmawati (Agrikan Jurnal Agribisnis Perikanan, 2025)
Tuna and skipjack tuna are capture fishery commodities that have a strategic role for the fisheries sector in Indonesia. The potential of skipjack tuna which is the target of fishing by fishermen in Nabire Regency has not been fully studied in detail so that data sources for the utilization of skipjack tuna are very limited and for the sake of sustainable utilization, a structured study is needed. The purpose of the study was to analyze the distribution of size and mature size of skipjack tuna gonads in Cenderawasih Bay. The research method applied survey methods and direct sample measurements in the field. The results showed that the size of skipjack tuna ranged from 25 - 52 cm. Male and female skipjack tuna were caught in mature gonad conditions and were caught a lot in TKG IV.